ダイ45ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 2004 - 阿保, 敏広; アボ, トシヒロ; 佐々木, 利; ササキ, サトシ; 海老田, 綾貴; エビタ, アヤタカ; 藤田, 建; フジタ, タツル; 久光, 純司; ヒサミツ, ジュンジ; Abo, Toshihiro; Sasaki, Satoshi; et al. (2008)
P(論文) この報告は第45次南極地域観測隊気象部門が,2004年2月1日から2005年1月31日まで昭和基地において行った気象観測結果をまとめたものである.観測方法,測器,統計方法等は第44次隊とほぼ同様である. 越冬期間中,特記される気象現象として,次のものが挙げられる.1) 月平均気温は7月と11月に平年を下回ったが,その他の月は平年並みか平年より高く経過した.特に2月7日の月最低気温-7.8℃は2月の高い値の極値を,12月の月平均気温0.2℃,最高気温月平均3.3℃は12月の高い値の極値を更新した.2) ブリザードは歴代8位の少なさであったが,発達した低気圧の相次ぐ接近により,6月は5.5回のブリザードとなり,月平均海面気圧980.5hPaは6月の低い値の極値を更新した.また,10月に来襲したA級ブリザードにより,10月としては過去最高の最大風速39.5m/s,最大瞬間風速49.3m/sを記録した.3) 2004年のオゾンホールの特徴は,面積,オゾン欠損量(破壊量)ともに,過去10年の中では2番目に小さく比較的小規模に推移した. This report describes the results of meteorological observations at Syowa Station from February 1st, 2004 to January 31st, 2005, carried out by the Meteorological Observation Team of the 45th Japanese Antarctic Research Expedition (JARE-45). The observation methods, instruments and statistical methods used by JARE-45 were almost the same as those used by the JARE-44 observation team.?Remarkable weather phenomena observed during the period of JARE-45 are as follows.1) The monthly mean temperatures were within the normals or above normal, except July and November in which monthly mean temperatures were below normal. Especially, the monthly minimum temperature of-7.8 degrees Celsius on February 7 sets a new maximum temperature for February; and both the monthly mean temperature of 0.2 degrees Celsius and the monthly mean daily maximum temperature of 3.3 degrees in Celsius were the highest recorded in December.2) The frequency of blizzards was the eighth lowest in history. However, in July, blizzards occurred 5.5 times beacause grown low pressure systems approached one after another, and the monthly mean sea level pressure of 980.5 hPa was the lowest recoreded in June. An A-class blizzard in October set both a new monthly maximum wind speed record of 39.5 m/s and a new monthly maximum instantaneous wind speed record of 49.3 m/s.3) The ozone hole in 2004 tended to be small in scale. Both the ozone hole area and ozone mass deficiency (depletion ozone mass) were the second lowest in the past decade. departmental bulletin paper